Fucoidan-Based Theranostic Nanogel for Enhancing Imaging and Photodynamic Therapy of Cancer - Cho, Mi Hyeon; Li, Yan; Lo, Pui‑Chi; Lee, Hyeri; Choi, Yongdoo (Nano-Micro Letters, 2020)
In this study, a fucoidan-based theranostic nanogel (CFN-gel) consisting of a fucoidan backbone, redox-responsive cleavable linker and photosensitizer is developed to achieve activatable near-infrared fluorescence imaging of tumor sites and an enhanced photodynamic therapy (PDT) to induce the complete death of cancer cells. A CFN-gel has nanomolar affinity for P-selectin, which is overexpressed on the surface of tumor neovascular endothelial cells as well as many other cancer cells. Therefore, a CFN-gel can enhance tumor accumulation through P-selectin targeting and the enhanced permeation and retention effect. Moreover, a CFN-gel is non-fluorescent and non-phototoxic upon its systemic administration due to the aggregation-induced self-quenching in its fluorescence and singlet oxygen generation. After internalization into cancer cells and tumor neovascular endothelial cells, its photoactivity is recovered in response to the intracellular redox potential, thereby enabling selective near-infrared fluorescence imaging and an enhanced PDT of tumors. Since a CFN-gel also shows nanomolar affinity for the vascular endothelial growth factor, it also provides a significant anti-tumor effect in the absence of light treatment in vivo. Our study indicates that a fucoidan-based theranostic nanogel is a new theranostic material for imaging and treating cancer with high efficacy and specificity. Highlights: 1 A fucoidan-based theranostic nanogel consisting of a fucoidan backbone, redox-responsive cleavable linker and photosensitizer enables activatable fluorescence imaging of tumor sites and an enhanced photodynamic therapy to induce complete death of cancer. 2 To use fucoidan as a polymeric backbone in the nanogel platform enables cancer targeting by P-selectin binding and enhances anti-tumor effect by inhibiting the binding of the vascular endothelial growth factor.